Versatility and modifications of the cross-finger flap in reconstruction of digital soft tissue defect - Ruhul Amin, M.; Nazrul Hossain Mullah, M.; Noor-E-Alam, M.; Khan, Aleem-Al-Razee; Nahar, Lailun; Ashiqur Rahman, M.; Nasrin, Shafia; Salah Uddin, M. (International Journal of Research in Medical Sciences, 2024)
Background: Hand injuries can cause major functional and cosmetic concerns. The cross-finger flap (CFF) is an effective treatment for complex finger defects. While CFF has typically been employed to treat volar aspect abnormalities, new versions now address a larger variety of digital soft tissue defects. The aim of the study was to evaluate the clinical outcome of various modified techniques of cross-finger flap which are used to reconstruct different soft tissue defect of fingers. Methods: This was a prospective observational study carried out in the department of Burn and Plastic Surgery at Dhaka Medical College Hospital, Dhaka from September 2018 to February 2020. Forty (40) patients who presented with different soft tissue defect of fingers included in this study according to inclusion and exclusion criteria. Results: The study involved predominantly male participants (80%), with a mean age of 31.70±14.28 years. The most common soft tissue defect site was the volar area (47.5%), and various modified cross-finger flap techniques were employed. The majority of patients achieved excellent functional outcomes, with 82.5% classified as good, 12.5% as satisfactory, and 5.0% as poor. Conclusions: The modifications of the cross-finger flap are versatile and useful for different sites of digital injuries with good functional outcome.